Virtual Reality-Based Interventions for Upper Limb Rehabilitation in Parkinson’s Disease: A Scoping Review and Critical Evidence Synthesis - Krishnendu P. G.; Riyas Basheer K. B.; Ismail Hazim; Athul Krishna K. R.; Subhashchandra Rai; Femina Hameed V. A.; Nishka S. Bolar; Mohammed Sanabin (Asian Journal of Medicine and Health, 2026)
Upper-limb dysfunction in Parkinson’s disease compromises dexterity, movement scaling, coordination and the performance of everyday tasks, yet rehabilitation research has historically prioritised gait and balance. Virtual reality (VR) can deliver repetitive, task-specific practice with augmented feedback, adaptable challenge and game-based engagement, but the clinical value of VR specifically for arm and hand rehabilitation remains uncertain. This scoping review mapped and critically synthesised evidence on VR-based interventions and VR-enabled assessment relevant to upper-limb rehabilitation in adults with Parkinson’s disease. Searches covered peer-reviewed literature from 2010 to 18 June 2026, with earlier seminal work retained where necessary for conceptual context. Evidence was organised by VR modality, therapeutic target, outcome domain, feasibility and methodological quality. The direct intervention literature remains small and heterogeneous, spanning non-immersive exergaming, optical hand tracking, fully immersive head-mounted systems and experimentally manipulated sensory feedback. Across small trials and feasibility studies, trained measures of movement speed, coordination, dexterity, strength or proprioception often improved, and adherence and acceptability were generally favourable. Nevertheless, the best current comparative evidence does not establish superiority of immersive VR over dose-matched conventional upper-limb training. Improvements in game performance frequently exceeded transfer to standardised clinical outcomes, and evidence for sustained gains, everyday activity, participation and quality of life is sparse. Methodological weaknesses include small samples, heterogeneous comparators and intervention doses, inconsistent medication-state reporting, short follow-up, fragmented outcome selection and limited safety reporting. VR is therefore best regarded as a promising delivery format and adjunct for intensive upper-limb practice rather than a proven superior treatment. Future trials should use adequately powered multicentre designs, active dose-matched comparators, blinded outcome assessment, standardised reporting of training dose and feedback, meaningful activity-level outcomes and longer follow-up, while explicitly testing whether immersion, sensorimotor feedback or adaptive game mechanics add benefit beyond equivalent conventional practice.